Values of serum intestinal fatty acid-binding protein, fecal calprotectin, and fecal human β-defensin 2 for predicting necrotizing enterocolitis - Sujia Liu; Yongle Liu; Shuhua Lai; Yingling Xie; Wenlong Xiu; Changyi Yang (BMC, 2024)
Abstract Background This study aimed to assess the diagnostic potential of serum intestinal fatty acid-binding protein (I-FABP), fecal calprotectin (FC), and fecal human β-defensin 2 (hBD2) in predicting necrotizing enterocolitis (NEC) in preterm infants. Methods A prospective cohort of neonates with a gestational age < 32 weeks, suspected of NEC, was enrolled between June 2021 and December 2022. Serum I-FABP, FC, and fecal hBD2 levels were measured upon NEC suspicion, and diagnosis was confirmed through radiological examination or surgical intervention. Diagnostic precision of serum I-FABP, FC, and fecal hBD2 was assessed using a logistic regression model with multiple variables. Results The study included 70 neonates (45 males, 25 females), with 30 developing NEC (40% Stage III, n = 12; 60% Stage II, n = 18) and 40 in the control group. NEC patients exhibited significantly higher serum I-FABP and FC levels (4.76 ng/mL and 521.56 µg/g feces, respectively) than those with other diagnoses (1.38 ng/mL and 213.34 µg/g feces, respectively; p ˂ 0.05 for both biomarkers). Stage II NEC neonates showed elevated fecal hBD2 levels (376.44 ng/g feces) than Stage III NEC neonates and controls (336.87 ng/g and 339.86 ng/g feces, respectively; p ˂ 0.05). No such increase was observed in infants progressing to Stage III NEC. Using a serum I-FABP threshold of > 2.54 ng/mL yielded 76.7% sensitivity, 87.5% specificity, 82.1% positive predictive value (PPV), and 83.3% negative predictive value (NPV). For FC (cutoff > 428.99 µg/g feces), corresponding values were 76.7% sensitivity, 67.5% specificity, 63.9% PPV, and 79.4% NPV. Conclusion Serum I-FABP and FC levels are valuable for early NEC detection and provide insights into disease severity. Low fecal hBD2 levels suggest an inadequate response to luminal bacteria, potentially rendering these infants more susceptible to NEC development or exacerbation.